2002
DOI: 10.1002/ana.10453
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hydrocephalus in rats and humans: White matter loss and behavior changes

Abstract: Chronic hydrocephalus that begins in childhood and progresses only very gradually is sometimes called "arrested" hydrocephalus. Data suggest that this state eventually can become symptomatic and may be treatable by shunting. However, the pathological substrate of the disorder is not entirely understood. We studied chronic hydrocephalus in rats, 9 months after induction by kaolin injection into the cisterna magna, and in humans. In both circumstances, destruction of periventricular white matter structures was w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
140
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(151 citation statements)
references
References 44 publications
10
140
1
Order By: Relevance
“…This suggests an attempt of to remyelination. These data are in agreement with the work of Del Bigio 18 and Lopes 19 . Further studies are needed to better understand the pathophysiology of hydrocephalus lesions produced in the corpus callosum and other structures of the brain parenchyma.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests an attempt of to remyelination. These data are in agreement with the work of Del Bigio 18 and Lopes 19 . Further studies are needed to better understand the pathophysiology of hydrocephalus lesions produced in the corpus callosum and other structures of the brain parenchyma.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, while decreased surface area and neocortical volume tend to follow an anterior to posterior gradient of increasing group differences and increased variability within the SB group, neocortical volume in the frontal region is similar between both groups. This finding is consistent with published studies of animal models of hydrocephalus and post mortem studies of humans with hydrocephalus where destruction of periventricular white matter was associated with increased ventricular size and the frontal region was predominately spared (Del Bigio et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, MRI assessment has revealed that agerelated loss of white matter is more significant than that of gray matter (Guttmann et al, 1998;Jernigan et al, 2001). Recent studies using Diffusion Tensor Imaging (DTI) reported that white matter was connected to cognitive functions, and ultrastructural changes in the integrity of white matter were very responsive to cognitive changes during aging (Del Bigio et al, 2003;Nagy et al, 2004;Shenkin et al, 2005;Huang and Auchus, 2007). Since the integrity of white matter tract relies mostly on the integrity of myelin sheaths, it can be inferred that myelin sheaths integrity is sensitive to aging.…”
Section: Introductionmentioning
confidence: 99%